Third training workshop on research to inform agricultural and food security policy and practice in Kenya, 16-19 July 2018 - Karugia, Joseph T. (2018)
The International Livestock Research Institute (ILRI) and the Swedish AgriFoSe2030 programme, are implementing an initiative to develop the capacity of recent PhD graduates to undertake policy relevant research and analysis and disseminate their work to the policy-making community in support of agriculture and food security in Kenya. In this regard, ILRI and AgriFose2030 organized the third and the last training workshop titled “Research to inform agricultural and food security policy and practice in Kenya” at ILRI Campus, Nairobi on 16th – 19th July 2018. This report is a record of the proceedings of the workshop and a summary of participants’ evaluation of the series of capacity building workshops.